Ruang Lingkup Kewenangan Peradilan Agama Dalam Mengadili Sengketa Ekonomi Syariah - Rahmi, Diana (Universitas Islam Negeri Antasari Banjarmasin, 2013)
After the implementation of the Act No. 3 year 2006, the dispute of Islamic Economic is absolutely included as the domain of the Islamic Courts competence, and would be entirely resolved by this court as well. However, some regulations recently lead to reduce this competence belongs to the Islamic Court by making this court not the only institution to resolve the dispute of Islamic Economic. In fact, the domain of the Islamic Court that is extended to settle all the Islamic Economic disputes, is also reduced by a clause that potentially indicate to resolve the dispute outside from the Islamic Court (as stated in the contract), and also by a conflict settled on the of Islamic arbitration.